Preferred mineral orientation of a chloritoid-bearing slate in relation to its magnetic fabric. (February 2015) - Haerinck, Tom; Wenk, Hans-Rudolf; Debacker, Timothy N.; Sintubin, Manuel
Abstract: A regional analysis of the anisotropy of the magnetic susceptibility on low-grade metamorphic, chloritoid-bearing slates of the Paleozoic in Central Armorica (Brittany, France) revealed very high values for the degree of anisotropy (up to 1.43). Nonetheless, high-field torque magnetometry indicates that the magnetic fabric is dominantly paramagnetic. Chloritoid's intrinsic degree of anisotropy of 1.47 ± 0.06, suggests that chloritoid-bearing slates can have a high degree of anisotropy without the need of invoking a significant contribution of strongly anisotropic ferromagnetic ( s.l. ) minerals. To validate this assumption we performed a texture analysis on a representative sample of the chloritoid-bearing slates using hard X-ray synchrotron diffraction. The preferred orientation patterns of both muscovite and chloritoid are extremely strong (∼38.6 m.r.d. for muscovite, 20.9 m.r.d. for chloritoid) and display roughly axial symmetry about the minimum magnetic susceptibility axis, indeed suggesting that chloritoid may have a profound impact on the magnetic fabric of chloritoid-bearing rocks. However, modeling the anisotropy of magnetic susceptibility by averaging single crystal properties indicates that the CPO of chloritoid only partially explains the slate's anisotropy. Highlights: The muscovite/chloritoid axial symmetric pole figure patterns reflect pure flattening. The muscovite and chloritoid textures show an extremely strong preferred orientation. Chloritoid has a profound impact on the magnetic fabric of the investigated slate. The calculated (from mineral textures) and measured degree of anisotropy do not match.